Yield of a subtropical pasture mixture under continuous and rotational grazing - Irulegui, Gustavo Schuler de; Maraschin, Gerzy Ernesto; Riboldi, João (Pesquisa Agropecuaria Brasileira, 2014)
A mixture of Desmodium intortum (Mill.) Urb. and Paspalum guenoarum Arech. was evaluated under a continuous and two rotational grazing systems with 14 and 42 days rest (DR), both with seven days of grazing. The mixture was evaluated through dry matter (DM) production, botanical composition, forage quality, stocking rate (SR), consumption and animal performance. The rotational grazing treatments were similar in DM production and both superior to the continuous grazing. The 42-DR treatment maintained the highest percentage of D. intortum and P. guenoarum and the lowest percentage of other grasses while 14-DR and continuous grazing were not different. The better mixture quality and consumption of the 42-DR treatment allowed higher average daily gain (ADG) per animal and liveweight gain (LWG) per hectare, compared to the 14 DR and continuous grazing. The higher SR supported by the 14-DR accounted for the higher consumption of Total Digestible Nutrients per hectare which brought this treatment to a level of magnitude very close to the 42 DR in terms of LWG per hectare. The lack of replications impaired the correct analysis of ADG per animal and LWG per hectare.
Keywords: Pastures; Desmodium intortum (MilI.) Urb.; Paspalum guenoarum Arech.; grazing management systems; dry matter production; botanical composition; forage quality; animal production